Moral Self and Identity in Children, Adolescents, and Adults <subtitle>A Measurement Invariance Examination</subtitle> - Neele Bäker; Jule Eilts; Jessica Wilke (Psychological Test Adaptation and Development)
Abstract: Research on morality, particularly on moral self and identity, is gaining increasing attention. However, the current literature reveals a lack of clarity in terminology, resulting in inconsistent operationalizations and instruments for studying moral self and identity. Specifically, there is a shortage of validated German-language instruments for measuring these constructs. This study provides new insights into the assessment of moral self and identity across different age groups – middle childhood, adolescence, and adulthood – through the testing of a German instrument. The results indicate partial measurement invariance between the three groups.